Pengaruh Dukungan Sosial Orang Tua Terhadap Motivasi Berprestasi - Fredericksen Victoranto Amseke (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
Achievement motivation is really important in education. There are external and internal factors that influence achievement motivation. One of the external factors is social support from parents. The purpose of this research is to know the influence of the parental social support toward the achievement motivation of the student in grade VII SMP Negeri 1 Biboki Kabupaten Timor Tengah Utara Kefamenanu. This research is an explanation research that aims to explain the causal influence of two variables in this study. The population is students grade VII SMP Negeri 1 Biboki Kabupaten Timor Tengah Utara Kefamenanu amounted 64 students, while the technique of sample used in this study is the saturation sample, meaning the use of all members within a population, which means this study involved 64 students as a sample. Results of the study show that there are positive and significant influences of the parental social support toward the achievement motivation of the student in grade VII SMP Negeri 1 Biboki Kabupaten Timor Tengah Utara Kefamenanu.